Shortwave Radiation on Horizontal and Incline Surfaces—One Year of Solar Radiation Measurements at Athalassa, an Inland Location in Cyprus - Pashiardis, Stelios; Kalogirou, Soteris A.; Pelengaris, Alekos (My University, 2022)
Athalassa is the main actinometric station of Cyprus and is located in the center of the island at a height of about 160 m. The station is equipped with shortwave and longwave radiation instruments. The time step of the measurements is 10 min, and hourly and daily values were derived for the period of June 2020–May 2021. The solar data underwent an extensive quality control process based mainly on the suggested tests of Baseline Surface Radiation Network (BSRN) for both the hourly and daily datasets. More than 98% of the data were within the limits recommended by the BSRN and other radiation networks. A statistical analysis of the shortwave solar radiation components was then performed. Linear and quadratic relationships were established between various radiation components, and their diurnal and monthly variability was assessed. The annual average daily global radiation amount was approximately 19 MJ/m2, whereas the amounts of horizontal beam and diffuse radiation were 12.9 MJ/m2 and 4.7 MJ/m2, respectively. Regarding the modeling of diffuse irradiance, the BRL diffuse fraction model (Boland-Ridley-Lauret) was applied. The results showed that the BRL model can satisfactorily estimate both the diffuse solar irradiance as well as the direct normal irradiance. Furthermore, the levels of the shortwave components were estimated based on the classification of four categories of the clearness index. The annual average of the direct normal beam radiation on clear days was 27.3 MJ/m2, and the direct horizontal radiation was 17.7 MJ/m2. Finally, the total energy received by an inclined surface was estimated based on measurements on the horizontal surfaces. In practice, photovoltaics were installed with an annual permanent slope of 26° with respect to the horizontal surface, and in a southern direction.
Keywords: Shortwave radiation measurements; Quality control; Statistical analysis; Energy on inclined surfaces; Cyprus